Development of LKPD on Fraction Material: Open-Ended Approach At State Elementary School 6 Susoh - Rizki Anggilia; Orin Asdarina (STMIK Indonesia Banda Aceh, 2025)
The purpose of the study was to produce student worksheets (LKPD) on fraction material based on open-ended learning. This type is included in development research using the ADDIE model, consisting of the stages of analysis , design , development , implementation , and evaluation . The subjects used were grade VI students of SD Negeri 6 Susoh, Southwest Aceh Regency, 2024-2025 academic year. The results of expert validation of LKPD based on open-ended is included in the valid category with an average score of 3.9 (good). Based on the results of the trial on students, the answers obtained with an average percentage of 93.18% with a good classification. This shows that students find it easier to understand fraction material if the LKPD is designed with an open-ended approach . The results of the development of LKPD based on open-ended are useful for learning in class 6 of SD Negeri 6 Susoh, Aceh Barat Daya Regency, as evidenced by the achievement of a learning completion rate of 72.73%.